The Essence of the Thing: a novel - St John M. Madeleine (New York, Carroll & Graf Publishers, Inc., 1998)
A novel by the author of Women in Black and A Pure Clear Light. It concerns things that women will do to hold on to love and things men will do to esape it. Having been told by her partner that they should separate, Nicola returns from the off-licence to find him changed from the man she knew.